Pengaruh penguasaan momentum terhadap hasil belajar fisika materi pokok dinamika rotasi siswa kelas XI IPA SMA Negeri 1 Batangtoru - Siregar, Sri Wahyuni; Siregar, S.Pd., M.Pd, Dedes Asriani (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
This study aims to find out momentum mastery and the rotation dynamics achievement of the XI IPA SMA Negeri 1 Batangtoru. Type of research is descriptive. The population is all of XI IPA SMA Negeri 1 Batangtoru. Consist of 3 parallel classes and total is 128 students. Sampling technique by using cluster sampling, it is 40 students. From the calculation, shows that the mean of momentum mastery is 65,68. It is enough category. The mean of rotation dynamics achievement is 71,38 it is good category.based on the calculation in inferential analysis, it is found thet t count is 0,347 an if it is compared to t table in 95% significant, it is found 0,3124. After comparing t count and t table, it is got that t count is greater than t table (0,347>0,3124). The hypothesis is accepted. Means that there is significant influence momentum mastery and the rotation dynamics achievement of XI IPA SMA Negeri 1 Batangtoru.